Transformasi Digital Desa Melalui Pembangunan Website dan Digitalisasi UMKM di Desa Tanjung Lago, Kabupaten Banyuasin - M. Soekarno Putra; Rio Fernando; Tabi In Athyam Madani; M. Rizki Julianto; Kgs. M.Fijai Fahlevi; Rindi Rama Saputra6; Edy Irawansyah; Muhammad Faiz; Aldi Saputra (Indo Publishing, 2025)
Digital transformation at the village level is a strategic step to enhance public service efficiency and empower the local economy. This community service program aims to support the digitalization process in Tanjung Lago Village through two main approaches: the development of an official village website as an information and governance transparency tool, and the digital empowerment of local small and medium enterprises (SMEs) producing kemplang, a traditional fish-based snack. The implementation methods included field observation, interviews, digital media design, website development, training sessions, and stakeholder validation. The village website was built using static web technology (HTML, CSS, JavaScript), featuring village profiles, activity galleries, organizational structure, and contact information. Meanwhile, the SME assistance focused on branding, packaging, product photography, and the use of social media for digital promotion. The results indicated improved capacity among village officials in managing public information and increased knowledge among SMEs regarding modern marketing strategies. This program successfully integrates information technology with local potential, contributing to inclusive and sustainable digital village development..